Chromosome analysis of walking catfish, Clarias spp. - Siraj, Siti Shapor; Sukardi, Ratiah; Cheah, Cheryl Phaik Imm; Khew, Huai Mei; Vellasamy, Shalini; Panandam, Jothi Malar; Daud, Siti Khalijah (Malaysian Society of Applied Biology, 2009)
Karyotyping is one of the useful tools for species identification, taxonomy, evolutionary and breeding selection. To date, no information on karyotyping of this fish in the country is documented. The aim of this study was to determine and differentiate the karyotypic structure and fundamental arm number of the walking catfish; Clarias macrocephalus, Clarias batrachus and Clarias gariepinus. The fish samples ranging from 23–160gm in weight and 16–40cm in length were used to obtain the chromosomes by subjecting to a combination of colchicine and phytohaemagglutinin for arresting a mitotic division. The karyotype of each species was arranged according to size, type and structure such as metacentric (M), submetacentric (SM), subtelocentric (ST) and acrocentric/telocentric (A/T). The diploid chromosome numbers ranged from 2n equal to 54 (Clarias macrocephalus and Clarias batrachus) to 2n equal to 56 (Clarias gariepinus).